2020
DOI: 10.1021/acsaem.9b02152
|View full text |Cite
|
Sign up to set email alerts
|

Dopant-Free Hole-Transport Materials Based on 2,4,6-Triarylpyridine for Inverted Planar Perovskite Solar Cells

Abstract: New building blocks of cores and periphery groups for organic hole-transporting materials (HTMs) have been paid much attention for recent development in perovskite solar cells (PSCs). In this work, we applied facile synthesis to join a 2,4,6-triarylpyridine building block for new HTMs based on a pyridine core by cheap industrial initial materials. The three small molecules, namely, D104, D105, and D106, were used in the pristine state. To the best of our knowledge, pyridine-cored dopant-free HTMs have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 51 publications
(88 reference statements)
0
30
0
Order By: Relevance
“…After 30 days in ambient conditions, the photovoltaic efficiency of the cells reduced by only 20%. Duan et al [144] improved the device performance and stability by incorporating 2,4,6-Triarylpyridine as an HTM to p-i-n PSCs.…”
Section: Sams For Improving Perovskite Solar Cells Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 days in ambient conditions, the photovoltaic efficiency of the cells reduced by only 20%. Duan et al [144] improved the device performance and stability by incorporating 2,4,6-Triarylpyridine as an HTM to p-i-n PSCs.…”
Section: Sams For Improving Perovskite Solar Cells Stabilitymentioning
confidence: 99%
“…Duan et al. [ 144 ] improved the device performance and stability by incorporating 2,4,6‐Triarylpyridine as an HTM to p‐i‐n PSCs.…”
Section: Sams For Improving Perovskite Solar Cells Stabilitymentioning
confidence: 99%
“…The pyridine moiety in these HTM can act as a Lewis base and which in turn can assist defect passivation of perovskite and π-conjugation effect. [24][25][26][27][28] Besides the core of HTMs, the arm is also vital for optimizing the semiconducting properties of HTMs. Up to now, the 6 -tetrakis(4-methoxyphenyl)-9H-carbazole-3,6-diamine) (DANCBZ) moiety have been demonstrated to be a valuable arm for the designing of molecular HTMs owing to their superior charge-transporting ability, stability and low-cost.…”
Section: Independently Reportedmentioning
confidence: 99%
“…Till now, many studies have shown that pyridine unit could passivate the interface defects effectively and enhance the hole extracting and transporting capability [15,16]. In our previous study, we have tried to introduce pyridine as terminal group to linear HTM, which induces enhanced chemical interaction between perovskite and HTM [17].…”
Section: Introductionmentioning
confidence: 99%